Visualization of invisible cell-death sign by electric-double-layer modulation - Jun'ya Tsutsumi; Jun Kurosu; Kaname Kanai; Kingo Uchida; Kana Morishita; Kimio Sumaru (Biosensors and Bioelectronics: X, 2023)
Leakage and self-spreading of a cytoplasmic lipid droplet in association with cell death, which was totally invisible in a conventional optical microscope, was discovered by using the recently developed electric-double-layer modulation imaging (EDLMI). The method allowed real-time imaging of the leaked lipid droplet with the thickness of a few nanometers. We demonstrate that the discovered phenomenon is useful as a new cellular sign for diagnosis of cell death.